A computational fluid dynamics study of flame gas sampling in horizontal dilution tubes. (30th June 2022) - Mätzing, Hartmut; Vlavakis, Petros; Trimis, Dimosthenis; Stapf, Dieter
Abstract: Abstract : The performance of horizontal dilution tubes is investigated by Reynolds-averaged Navier–Stokes and large-eddy simulations. The flame gas enters the dilution tube through a pinhole. The orifice flow and the dilution process inside the tube are studied. The volume flow through the orifice is shown to be proportional to the square root of the pressure drop. The discharge coefficient is 0.9 ± 0.3 in the cold air (calibration) case and drops to 0.35 under hot (flame) conditions. The resulting dilution ratio is roughly a factor of five below typical literature data. The gas sample remains in the wall boundary layer and the mixing process is not complete at the end of the dilution tube. Turbulence decays rapidly behind the tube inlet, which shifts the flow into the laminar to turbulent transition regime. Turbulence increases significantly in the outlet section which has much smaller pipe cross-sections. Despite its relatively low Reynolds number, the outlet flow to the particle sizer (or to the gas analyzer) is clearly turbulent, and interactions with the wall are probable. The results are in agreement with previous findings from laminar jets in cross-flow. Guidelines for optimization of the sampling conditions are suggested.